Beyond the acronym, POEMS syndrome, a multisystemic enigma: a case report and comprehensive evidence-based perspective - Gómez-Piña, Juan José; Castro Luna, Vanessa; Arroyo Chávez, Alan David; Soria Elicea, Mario; Domínguez Hernández, Edgar Ulises; Arguello Trenado, Juan Carlos; Olvera Acevedo, Arturo (International Journal of Research in Medical Sciences, 2025)
The POEMS syndrome (Polyneuropathy, Organomegaly, Endocrinopathy, M protein and Skin changes) is a rare and complex disease involving a variety of body systems. Emphasis is placed on peripheral neuropathy and the presence of a monoclonal protein. Additionally, major and minor criteria, including bone lesions, elevated VEGF and Castleman’s disease, are significant factors. On the therapeutic front, options range from radiotherapy to systemic therapy, underscoring the importance of an early treatment response. A 64-yearsold diabetic male, complain with weakness in lower limbs, along with edema and hyperpigmentation. He is diagnosed with neuropathy and CIDP is confirmed in EMG. An abdominal CT scan reveals hepatomegaly. Elevated proteins are identified as a finding in the liver function tests. Subsequent serum electrophoresis confirms an increase in M protein. Treatment with bortezomib and dexamethasone is initiated, resulting in clinical improvement. Despite this progress, the patient discontinues follow-up appointments. The POEMS syndrome is a diagnostic challenge, especially when primary symptom is polyneuropathy. The main key to diagnosis is the identification of the M protein through electrophoresis and immunofixation. A multidisciplinary diagnostic remains essential in addressing its complexity.